2019
DOI: 10.7567/1347-4065/aafd8e
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth of a MnS buffer layer for non-polar AlN on Si (100) deposited by radio frequency magnetron sputtering

Abstract: The growth conditions of MnS thin film on a Si (100) substrate deposited by the RF-magnetron sputtering method were investigated. The MnS is a buffer layer for the epitaxial growth of non-polar AlN thin film on the Si (100) substrate. The 4°-off-Si (100) substrate and the insertion of MnS film grown at room temperature (RT-MnS) improved the crystallinity and the surface roughness of the MnS film. In particular, the 20 nm thick RT-MnS showed a reduction of surface roughness of the MnS layer deposited at 550 °C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Our previous report revealed that the use of 4°-off-Si improves the crystallinity of MnS films. 24) 4°-off-Si was treated with HF solution after cleaning with an organic solvent and pure water. First, an initial 20 nm Zn x Mn 1−x S or MnS layer was deposited by radio frequency (RF) magnetron sputtering using MnS and ZnS sintered ceramic targets (Kojundo Chemical Laboratory, 2N and 4N grades, respectively) on 4°-off-Si at room temperature (hereafter, RT-Zn x Mn 1−x S and RT-MnS), because, according to our previous report, RT-MnS improved the crystallinity of MnS (100) films.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous report revealed that the use of 4°-off-Si improves the crystallinity of MnS films. 24) 4°-off-Si was treated with HF solution after cleaning with an organic solvent and pure water. First, an initial 20 nm Zn x Mn 1−x S or MnS layer was deposited by radio frequency (RF) magnetron sputtering using MnS and ZnS sintered ceramic targets (Kojundo Chemical Laboratory, 2N and 4N grades, respectively) on 4°-off-Si at room temperature (hereafter, RT-Zn x Mn 1−x S and RT-MnS), because, according to our previous report, RT-MnS improved the crystallinity of MnS (100) films.…”
Section: Methodsmentioning
confidence: 99%
“…First, an initial 20 nm Zn x Mn 1−x S or MnS layer was deposited by radio frequency (RF) magnetron sputtering using MnS and ZnS sintered ceramic targets (Kojundo Chemical Laboratory, 2N and 4N grades, respectively) on 4°-off-Si at room temperature (hereafter, RT-Zn x Mn 1−x S and RT-MnS), because, according to our previous report, RT-MnS improved the crystallinity of MnS (100) films. 24) The base pressure was 4.1 × 10 -6 Pa, and the Ar gas pressure and RF sputtering power were set to 2.0 Pa and 150 W, respectively. On these films, 30 nm composition-spread Zn x Mn 1−x S films were deposited at 550 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] These films were deposited on SiO 2 glass substrates via spontaneous nucleation, which is one of the characteristics of sputtering. Recently, sputtering was used to obtain non-polar m-axis-oriented AlN films on a Si(100) substrate with a MnS buffer layer 24 and nonpolar a-axis-oriented AlN films on an r-plane sapphire substrate, 25 both of which exhibited epitaxial growth regimes. The successful fabrication of these films proves the potential of the sputtering technique for promoting epitaxial growth to construct devices comprising non-polar AlN-based layers.…”
Section: Introductionmentioning
confidence: 99%